PENGARUH PERBANDINGAN TEPUNG AMPAS TAHU DENGAN TERIGU TERHADAP KARAKTERISTIK FLAKES - Diah Ratna Sari, Dewa Ayu Putu; Wisaniyasa, Ni Wayan; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2015)
This study aims were to determine the effect of tofu waste flour and wheat flour on the characteristic of flakes and to find out the best ratio of tofu waste flour and wheat flour that produce flakes with the best characteristic. The design of research was Completely Random Design (CRD). The treatment factor was ratio of tofu waste flour and wheat flour with 5 levels : 20%:80%, 25%:75%, 30%:70%, 35%:65% and 40%:60%. Each treatment was repeated three times in order to obtain 15 experimental units. The results showed that the ratio of tofu waste flour and wheat flour in the production of flakes has effect on the water content, ash content, protein content, fat content, carbohydrate content, crude fiber content, color, flavor, taste, texture and overall acceptability. Ratio of 40% tofu waste flour and 60% wheat flour produced flakes with the best characteristic with 1,31% water content, 2,97% ash content, 13,01% protein content, 10,73% fat content, 71,99% carbohydrate content, 7,64% crude fiber content, color (liked), flavor (liked), taste (liked), texture (liked) and overall acceptability (liked)
Keywords: wheat flour, tofu waste flour, flakes